Analisis Hukum Penanganan Kasus Pidana dengan Pelaku oleh Kepolisian dengan Pendekatan Restorative Justice (Studi di Polsek Medan Baru) - Harahap, M. Yarhamuddin; Ahmad, Akiruddin; Sahbudi, Sahbudi (Universitas Medan Area, 2025)
The juvenile criminal justice system in Indonesia, as regulated by Law Number 11 of 2012 on the Juvenile Criminal Justice System, Supreme Court Regulation Number 4 of 2014, and Police Regulation Number 8 of 2021, emphasizes the application of a restorative justice approach as an alternative to resolving cases involving children. This study employs an empirical juridical research method with normative and sociological approaches. Data were collected through literature review and interviews with police officers at the Medan Baru Police Sector. The research examines: (1) the legal framework governing restorative justice in Indonesian criminal law; (2) its implementation by investigators toward juvenile offenders at the Medan Baru Police Sector; and (3) the factors hindering its implementation. The findings indicate that restorative justice has a strong normative legal foundation. Its implementation at the Medan Baru Police Sector is carried out through diversion by prioritizing the best interests of the child and facilitating mediation between the offender, the victim, their families, and related parties. However, several obstacles remain, including limited resources, lack of public understanding, and technical constraints in the mediation process. Therefore, enhanced socialization, improved facilities, and active community participation are necessary to optimize the implementation of restorative justice in ensuring legal protection for children.